Natural Resources, Technology Improvements, and Growth - Fidel Perez-Sebastian; Ohad Raveh; Frederick van der Ploeg (Environmental and Resource Economics, 2025)
We study, analytically and empirically, how technological changes affect the nexus between resource abundance and economic growth. Our two-sector model indicates that capital-augmenting technological improvements can be contemporaneously contractionary in resource-rich economies, and expansionary elsewhere, due to differences in the size of the elasticity of substitution between labor and capital. In addition, such improvements yield relatively steeper expansionary patterns in resource-rich economies in the longer run. We test these predictions using a panel of U.S. states and counties. Our identification strategy rests on geographically-entrenched differences in resource endowments, and the adoption of plausibly exogenous technology shocks at the national level. Our core estimates corroborate our predictions. First, we document persistent differences in the elasticity of substitution between capital and labor across the natural-resource dimension. Second, we find that an increase in TFP is on impact contractionary in resource-rich states, but is non-contractionary (at worst) in resource-poor ones. Third, we illustrate that in the longer term a positive technology shock expands output and inputs in resource-rich economies relatively more strongly. Our results shed light on hitherto overlooked potential adverse effects of natural resource abundance.
Keywords: Q32; E32; O33; 330; Natural resource abundance; Technology shocks; Input elasticities